Health benefits and risks of fermented foods—the PIMENTO initiative - Todorovic, Smilja; Akpinar, Asli; Assunção, Ricardo; Bär, Cornelia; Bavaro, Simona L.; Berkel Kasikci, Muzeyyen; Domínguez-Soberanes, Julieta; Capozzi, Vittorio; Cotter, Paul D.; Doo, Eun-Hee; Gündüz Ergün, Burcu; Guzel, Mustafa; et al. (Frontiers in Nutrition, 2024)
Worldwide, fermented foods (FF) are recognized as healthy and safe. Despite the rapid increase of research papers, there is a lack of systematic evaluation of the health benefits and risks of FF. The COST Action CA20128 "Promoting innovation of fermented foods" (PIMENTO) aims to provide a comprehensive assessment on the available evidence by compiling a set of 16 reviews. Seven reviews will cover clinical and biological endpoints associated with major health indicators across several organ systems, including the cardiovascular, gastrointestinal, neurological, immune, and skeletal systems. Nine reviews will address broader biological questions associated with FF including bioactive compounds and vitamin production, nutrient bioavailability and bioaccessibility, the role of FF in healthy diets and personalized nutrition, food safety, regulatory practices, and finally, the health properties of novel and ethnic FF. For each outcome assessed in the reviews, an innovative approach will be adopted based on EFSA's published guidance for health claim submissions. In particular, each review will be composed of three parts: 1) a systematic review of available human studies; 2) a non-systematic review of the mechanism of action related to the clinical endpoints measured by the human studies identified in part 1; and 3) a non-systematic review of the characterization of the FF investigated in the human studies identified in part 1. The evidence and research gaps derived from the reviews will be summarized and published in the form of a strategic road map that will pave the way for future research on FF.